2019
DOI: 10.1002/hed.26041
|View full text |Cite
|
Sign up to set email alerts
|

Rational genomic optimization of DNA detection for human papillomavirus type 16 in head and neck squamous cell carcinoma

Abstract: Background We aimed to use genomic data for optimizing polymerase chain reaction (PCR) primer/probe sets for detection of human papillomavirus (HPV)‐16 in body fluids of patients with HPV‐related head and neck squamous cell carcinoma (HPV‐HNSCC). Methods We used genomic HPV‐HNSCC sequencing data from a single institutional and a TCGA cohort. Optimized primer/probe sets were designed and tested for analytical performance in CaSki HPV‐16 genome and confirmed in salivary rinse samples from patients with HPV‐HNSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A polymerase chain reaction (PCR)–based test for HPV16 DNA in plasma and salivary rinses was performed on linked, deidentified samples in a Clinical Laboratory Improvement Amendments–certified laboratory at the Johns Hopkins Clinical Medical Microbiology Laboratory (Baltimore, Maryland), as previously reported . Assays were performed on 1 mL of plasma and a 0.5-mL aliquot of saliva rinse, which represented half of the centrifuged cell pellet from an 8-mL saline oral rinse, using primer probe combinations that targeted the E5L2 and E1 regions, as well as the E7 region .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A polymerase chain reaction (PCR)–based test for HPV16 DNA in plasma and salivary rinses was performed on linked, deidentified samples in a Clinical Laboratory Improvement Amendments–certified laboratory at the Johns Hopkins Clinical Medical Microbiology Laboratory (Baltimore, Maryland), as previously reported . Assays were performed on 1 mL of plasma and a 0.5-mL aliquot of saliva rinse, which represented half of the centrifuged cell pellet from an 8-mL saline oral rinse, using primer probe combinations that targeted the E5L2 and E1 regions, as well as the E7 region .…”
Section: Methodsmentioning
confidence: 99%
“…A polymerase chain reaction (PCR)–based test for HPV16 DNA in plasma and salivary rinses was performed on linked, deidentified samples in a Clinical Laboratory Improvement Amendments–certified laboratory at the Johns Hopkins Clinical Medical Microbiology Laboratory (Baltimore, Maryland), as previously reported . Assays were performed on 1 mL of plasma and a 0.5-mL aliquot of saliva rinse, which represented half of the centrifuged cell pellet from an 8-mL saline oral rinse, using primer probe combinations that targeted the E5L2 and E1 regions, as well as the E7 region . Briefly, nucleic acid from plasma and oral rinse samples were extracted using the easyMag instrument (bioMerieux), input and elution volumes were 500 and 50 μL, and quantitative real-time PCR amplification was performed on a 7500 real-time PCR system for 3 genomic regions of HPV16.…”
Section: Methodsmentioning
confidence: 99%
“…Presence of high-risk HPV was determined using quantitative real-time PCR (qPCR) with highly selective primer-probe combinations (BR E1-5, HR E5L2-4, and E7) as previously described by our group. 14 Each reaction used 20 ng purified genomic DNA from saliva as template and was performed in triplicate. Reverse-transcribed full-length HPV genome was used as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…A 2020 paper by Saito et al demonstrated that detection of HPV16 DNA in salivary rinses can be improved using rational genomic design 55 . They hypothesized that previous detection studies had mediocre findings due to use of older, nonoptimized primer/probe sets that failed to utilize newer technological advances, including whole genome sequencing (WGS) and updated assay design.…”
Section: Salivary Biomarkers Of Hpv‐induced Opsccmentioning
confidence: 99%
“…A 2020 paper by Saito et al demonstrated that detection of HPV16 DNA in salivary rinses can be improved using rational genomic design. 55 They hypothesized that previous detection studies had mediocre findings due to use of older, nonoptimized primer/probe sets that failed to utilize newer technological advances, including whole genome sequencing (WGS) and updated assay design. They analyzed two datasets using WGS of HPV-positive head and neck squamous cell carcinoma and then designed rational primer/ probes that would result in optimal detection of HPV16.…”
Section: Dnamentioning
confidence: 99%